EMOSI POSITIF PADA IBU YANG MEMILIKI ANAK TUNAGRAHITA DI SLB C YPALB KARANGANYAR - Zahrotun 'Abiir; Isnanita Noviya Andriyani (Program Studi Bimbingan Konseling Islam, Fakultas Tarbiyah Dan Ilmu Keguruan, Institut Ummul Quro Al-Islami Bogor, 2023)
The phenomenon is related to mothers who have mentally retarded children in Indonesia feel sadness, disappointment, and other negative emotions. That way people can only see from the side of negative emotions. With this research, it aims to find out how the positive emotional picture of mothers who have mentally retarded children. The method in this study is qualitative with a phenomenological approach. The research results obtained are the existence of various forms of positive emotions in mothers who have mentally retarded children and the factors that influence these positive emotions. Knowing the various forms of positive emotions in mothers who have mentally retarded children and also the factors that influence these positive emotions, is expected to make the public know that mothers who have mentally retarded children not only have negative emotions but also positive emotions